Descrevendo a prática clínica junguiana no Brasil: quem somos, o que pensamos e o que fazemos nós, afinal? - Caetano, Aurea Afonso M (2016)
This study aim was to research Brazilian Jungian analysts concerning who we are, how we work and what we think about our clinical practice. We intended to verify where we work and who are our patients. We also aimed at investigating which are the most important theoretical concepts for our clinical practice, which specific therapeutic techniques we use and how do we feel about the work we accomplish. Given the current psychology studies interests on the new findings of neurosciences, it was also our goal to understand whether the Jungian psychotherapist demonstrate concerns regarding this issue and what is the real use of these concepts in our clinical practice. For this research we created a questionnaire with 18 multiple-choice questions, containing queries about the personal and professional profile of therapists, and an open question asking about the meaning of the work for them. The invitation letter was sent by email to participants: Jungian psychotherapists with different types of training, who currently work in Brazil. The chosen method for sample selection was convenience sampling and we achieved a total of 282 responses. in order o elaborate the survey, invite the participants and process the received data, we used a research application named SurveyMonkey ® Questionnaire results showed a significant majority of female therapists, a higher concentration of Jungian therapists in the southeast region of the country and a majority of therapists who have graduated over 30 years ago. As for currently being both in therapy and supervision the sample is equally divided. the vast majority of these therapists have a psychology degree; significant share of respondents have some type of specialization and only a few of then have a doctorate degree. The concepts of complex, self and individuation process come to light as the most important in this research while the practice and experience as therapists as well as personal analysis are among the most important requirements for a qualified Jungian professional. Working with dream interpretation is essential for all respondents, followed by the use of expressive techniques. A significant majority of the surveyed therapists work with adult patients and the main reason for the search of therapy is usually a personal crisis. The consulting room is the main space of practice, but consultation mediated by computer via Skype or Facetime have emerged as an important possibility. Professionals who competed the questionnaire are significantly connected to some kind of study group and consider scientific production in the area very important, managing to work on the production of papers. Considering the answers collected when participants are asked about the meaningfulness of their work, we found out that there are several different types of connections, allowing different possibilities for personal expressions through professional practice.